Partnership Strategy Patterns of Micro, Small, and Medium Enterprises in Increasing the Productivity of Crocodile Leather Artisans in Mimika Regency - Bertha Parrangan; Mesak Iek; Yundy Hafizrianda (LPPM STIE Krakatau, 2025)
Purpose: This study analyzes partnership strategies between MSMEs and stakeholders, particularly NGOs and financial institutions, to boost the productivity of crocodile leather craftsmen in Mimika Regency, Papua, focusing on market access, financial literacy, and sustainability. Methodology/approach: The research applies a qualitative descriptive case study approach. Data were collected through in-depth interviews, observation, and documentation involving MSME actors, local government agencies, and partner institutions. Thematic analysis was used to identify patterns, strengths, and challenges in collaborative practices. Results/findings: The findings show that strategic partnerships especially with NGOs and cooperative financial entities significantly improve production management, marketing outreach, and product value for local craftsmen. NGOs play a critical role in mentoring, capacity building, and ensuring sustainability through continuous engagement. However, the absence of formal contracts and inconsistent raw material supply remains a challenge. Conclusions: Collaborations with NGOs and financial institutions strengthen MSME capacity and market reach but require stronger institutional agreements to ensure resilience and sustainability. Limitations: The study is limited to one regency and focuses solely on crocodile leather MSMEs, with qualitative data restricting generalization. Contribution: This research offers a replicable partnership model for MSME empowerment in remote regions, combining financial inclusion with ongoing technical and managerial support.